Flowering and fruit set - Primo-Millo, Eduardo; Agustí, Manuel (Elsevier, 2021)
The most relevant aspects related to flowering, fruit set, and fruit development are reviewed in this chapter. In relation to flowering, special attention has been paid to the genetic, environmental aspects, particularly temperature and water stress, and to the endogenous factors, such as the nutritional status of the plant and the influence of the fruit as a decisive factor in alternate bearing. The main cultural practices to both reduce and increase flowering intensity are also reviewed. Fertilization and parthenocarpy are studied from an environmental, hormonal, and nutritional point of view, paying special attention to the competition phenomena between developing fruits, as a decisive factor in fruit setting and final fruit size. We also review the endogenous factors related to these processes and the most effective cultural practices to increase fruit set (the application of GA3 and girdling branches) and the final fruit size (the application of synthetic auxins). This chapter ends with the study of seed development.